Investigating the factors affecting outward FDI of Vietnam: Does political index matter? - Quang, Phung Thanh; Que, Hoang Xuan; Thao, Doan Phuong; Chau, Le Thi Quynh; An, Nguyen Thi Hoang (Edelweiss Applied Science and Technology, 2024)
Considering the important role of foreign direct investment (FDI) in economic growth and integration, this paper seeks to thoroughly analyze the outward FDI pattern of Vietnam to its 15 major FDI recipients (accounting for approximately 94% of Vietnam’s OFDI) using the gravity theory and a robust panel data approach for the comprehensive annual data over the period of 2007 – 2022. By determining the main destinations of Vietnam’s Outward FDI through the creation of social, economic, and political indices via the principle component analysis (PCA), the empirical results conclusively prove the positive impacts of the political index, social index, the existence of a common border, and accession to the WTO on the Vietnamese OFDI volume, while geographical distance is found to negatively impact the flow. As the main practical policy implications, issuing policies for sustainable economic growth, creating the novel strategy of FDI neighborhood policy, and fostering regionalism through FTAs (Free Trade agreements) are highly recommended.